Are teachers happy? a correlational study of emotional intelligence and psychological well-being - Mohamed Zaki, Nur Farhana; Ahmad, Nor Aniza; Tee, Ker Shin (Gokmen Arslan, 2022)
Teachers, alongside their fellow students, are essential entities in educational institutions and have a profound influence in the process of shaping the younger generations. The taxing demands of the job, coupled with the mental pressure, including stress, fatigue and depression, have led to a growing number of psychological ailments within the teaching profession. It is crucial to explore the determinants for teachers' psychological well-being, to ensure that they are equipped with effective coping mechanisms to deal with these work issues. In this research, the author aims to determine the level of emotional intelligence, as well as the psychological well-being of secondary school teachers. Furthermore, this research also intends to ascertain the connection between emotional intelligence and psychological well-being, and investigate the predictors for psychological well-being for teachers. To achieve these objectives, a correlational study by conducting a survey has been done using the Malay version of the Schutte Self-Report Emotional Intelligence Test (SSEIT) and Ryff Psychological Well-Being Scale (RPWB). This study was carried out in five schools involving 328 teachers which resulted in a significant relationship between emotional intelligence and psychological well-being. Simultaneously, mood regulations are the best predictor for psychological well-being among secondary school teachers. This research leads to a broadening of new dimensions of psychological well-being in education and affiliated institutions. By examining teachers' psychological well-being and the factors contributing to it, more interventions and approaches can be revised and introduced to increase teachers' job satisfaction and work-life balance.